(untitled) (Prithvi Academic Journal, 2026)
This study examined how the loans mediate the linkage between interest spread and non-performing loans (NPLs) in Nepali banks. The study took data from both public and private commercial banks currently operating in Nepal, and secondary data were sourced from Nepal Rastra Bank (NRB) over the period 2021Q3-2025Q2. Utilizing the stepwise regression estimator, finding discloses that interest spread substantially augment NPLs. The result shows that one percent increase/decrease in interest spread trigger 0.213 percent increase/decrease in NPLs. Conversely, the Capital Adequacy Ratio (CAR) reduces the credit risk. It showed that one percent increase/decrease in the CAR trigger 1.505 percent decrease/increase in NPLs. By contrast, liquidity, agriculture loans, and micro, cottage, small, and medium industries (MCSEM) loans amplify NPLs. It signifies that a one percent increase/decrease in liquidity, agriculture loans, and MCSEM triggers 0.891, 0.110, and 0.215 percent, respectively. The sensitivity, subgroup, and heterogeneity analysis also confirmed these findings. Finally, the result also confirmed that a rise in interest spread accelerates loan volume, and a rise in loan volume augments NPLs in Nepalese banks. The mediation effect is 0.097, which accounts for 45.54 percent of the total effect. The policymaker, such as NRB, could fix the lower limit and upper cap for interest spread, which can prevent banks from decreasing profitability and suffering higher NPLs. Bankers, on the other hand, could take more precautions about loan assessment and monitoring while granting loans with high interest spread.